(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
During strong earthquakes the nonlinear performance of building structures is determined by the response reduction factor (R) which is a seismic design parameter. Whereas, an extensive review of related literature indicates that the effect of viscous dampers on the response reduction factor is not considered. Therefore, this study proposed the response reduction factors for reinforced concrete structures equipped with viscous damper devices and investigated the effect of implementing such devices in reinforced concrete structures on the response reduction factor. Response reduction factor was formulated based on three aspects, namely, over strength, redundancy, and ductility factors. Fluid viscous damper is a device that enhances the performance of the building by adding damping. This study reviewed the recent developments in finding the influence of response reduction factor for RC framed buildings and their materials. Moreover, various approaches to pushover analysis and time history analysis have been mentioned in this review paper.